Acute Kidney Injury Is Common in Pediatric Severe Malaria and Is Associated With Increased Mortality. (26th February 2016) - Conroy, Andrea L.; Hawkes, Michael; Elphinstone, Robyn E.; Morgan, Catherine; Hermann, Laura; Barker, Kevin R.; Namasopo, Sophie; Opoka, Robert O.; John, Chandy C.; Liles, W. Conrad; Kain, Kevin C.
Abstract : Acute kidney injury is common in severe malaria and associated with short- and long-term mortality developing in 50% of cases after admission. Cystatin C and BUN are associated with the severity of AKI, are elevated at admission and predict mortality. Abstract: Background.  Acute kidney injury (AKI) is a well recognized complication of severe malaria in adults, but the incidence and clinical importance of AKI in pediatric severe malaria (SM) is not well documented. Methods.  One hundred eighty children aged 1 to 10 years with SM were enrolled between 2011 and 2013 in Uganda. Kidney function was monitored daily for 4 days using serum creatinine (Cr). Acute kidney injury was defined using the Kidney Disease: Improving Global Outcomes (KDIGO) guidelines. Blood urea nitrogen (BUN) and Cr were assessed using i-STAT, and cystatin C (CysC) was measured by enzyme-linked immunosorbent assay. Results.  Eighty-one (45.5%) children had KDIGO-defined AKI in the study: 42 (51.9%) stage 1, 18 (22.2%) stage 2, and 21 (25.9%) stage 3. Acute kidney injury evolved or developed in 50% of children after admission of hospital. There was an increased risk of AKI in children randomized to inhaled nitric oxide (iNO), with 47 (54.0%) of children in the iNO arm developing AKI compared with 34 (37.4%) in the placebo arm (relative risk, 1.36; 95% confidence interval [CI], 1.03–1.80). Duration of hospitalization increased across stages of AKI ( P = .002). Acute kidney injury was associated with neurodisability at discharge in the children receiving placebo (25% in children with AKI vs 1.9% in children with no AKI, P = .002). Mortality increased across stages of AKI ( P = .006) in the placebo arm, reaching 37.5% in stage 3 AKI. Acute kidney injury was not associated with neurodisability or mortality at discharge in children receiving iNO ( P > .05 for both). Levels of kidney biomarkers were predictive of mortality with areas under the curves (AUCs) of 0.80 (95% CI, .65–.95; P = .006) and 0.72 (95% CI, .57–.87; P < .001), respectively. Admission levels of CysC and BUN were elevated in children who died by 6 months ( P < .0001 and P = .009, respectively). Conclusions.  Acute kidney injury is an underrecognized complication in young children with SM and is associated with increased mortality.